Combination of Decitabine and a Modified Regimen of Cisplatin, Cytarabine and Dexamethasone: A Potential Salvage Regimen for Relapsed or Refractory Diffuse Large B-Cell Lymphoma After Second-Line Treatment Failure - Hu, Junxia; Wang, Xin; Chen, Fei; Ding, Mengjie; Dong, Meng; Yang, Wanqiu; Yin, Meifeng; Wu, Jingjing; Zhang, Lei; Fu, Xiaorui; Sun, Zhenchang; Li, Ling; et al. (Frontiers in Oncology, 2021)
Objective: The prognosis for patients with relapsed or refractory diffuse large B-cell lymphoma (R/R-DLBCL) after second-line treatment failure is extremely poor. This study prospectively observed the efficacy and safety of decitabine with a modified cisplatin, cytarabine, and dexamethasone (DHAP) regimen in R/R-DLBCL patients who failed second-line treatment. Methods: Twenty R/R-DLBCL patients were enrolled and treated with decitabine and a modified DHAP regimen. The primary endpoints were overall response rate (ORR) and safety. The secondary endpoints were progression-free survival (PFS) and overall survival (OS). Results: ORR reached 50% (complete response (CR) rate, 35%), five patients (25%) had stable disease (SD) with disease control rate (DCR) of 75%. Subgroup analysis revealed patients over fifty years old had a higher CR rate compared to younger patients (P = 0.005), and relapsed patients had a better CR rate than refractory patients (P = 0.031). Median PFS was 7 months (95% confidence interval (CI), 5.1-8.9 months). Median OS was not achieved. One-year OS was 59.0% (95% CI, 35.5%-82.5%), and two-year OS was 51.6% (95% CI, 26.9%-76.3%). The main adverse events (AEs) were grade 3/4 hematologic toxicities such as neutropenia (90%), anemia (50%), and thrombocytopenia (70%). Other main non-hematologic AEs were grade 1/2 nausea/vomiting (40%) and infection (50%). No renal toxicity or death occurred. Conclusion: Decitabine with a modified DHAP regimen can improve the short response and prognosis of R/R-DLBCL patients with good tolerance to AEs, suggesting this regimen has potential as a possible new treatment option for R/R-DLBCL patients after second-line treatment failure. (identifier: NCT03579082, website: Clinical Trials.gov)